KENDALA PENERAPAN PERTANGGUNGJAWABAN PIDANA KORPORASI SEBAGAI PELAKU TINDAK PIDANA KORUPSI (THE OBSTACLES OF IMPLEMENTING THE CRIMINAL LIABILITY OF THE CORPORATION AS A CRIMINAL OF CORRUPTION) - Puteri Hikmawati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2017)
The handling of corruption by the law enforcement officers do not yet optimally entangled the corporation as the perpetrator of a criminal act. Whereas, the Law concerning the Eradication of the Criminal Act of Corruption Law Number 31 year 1999 which has been amended by Law Number 20 year 2001 the has been regulated that the corporation as the subject of criminal act. However, only a few corporations have been convicted, one of them is the case involving PT Giri Jaladi Wana (PT GJW) in development of Sentra Antasari Market’s project in Banjarmasin. There are obstacles on implementing the corporate liability in corruption criminal act, as an example the case in this article. Part of the data used in the writing of this article is obtained from the results of research in North Sumatra Province and East Java Province. This article describes the lack of complementary provisions on corporate criminal liability in Law Number 31 year 1999, which causing difficulties in its application by the law enforcement officers. The Regulation of Attorney General Number PER-028/A/JA/10/2014 concerning the Guidance on Criminal Case Handling with Corporation As a Legal Subject and the Supreme Court’s Regulation Number 13 Year 2016 concerning the Standard Procedures for Handling Criminal Acts by Corporation, are considered to fill the legal vacant. However, the legal standing of The Attorney General Regulation and The Supreme Court’s Regulation are did not include as the types and hierarchy of legislation, which can only be recognized, therefore it is only bind internally. This article is expected to be inserted into the amendment of Law Number 31 year 1999, the Criminal Code, and Law Number 8 year 1981 on Criminal Code Procedures.ABSTRAKPenanganan korupsi yang dilakukan oleh aparat penegak hukum belum secara maksimal menjerat korporasi sebagai pelaku tindak pidana. Padahal, Undang-Undang Nomor 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi sebagaimana telah diubah dengan UndangUndang Nomor 20 Tahun 2001 tentang Perubahan Atas Undang-Undang Nomor 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi (UU Tipikor) telah mengatur korporasi sebagai subjek tindak pidana. Namun, sampai saat ini hanya beberapa korporasi yang dihukum sebagai terpidana korupsi, salah satunya kasus korupsi yang melibatkan PT Giri Jaladi Wana (PT GJW) dalam proyek pembangunan Pasar Sentra Antasari di Banjarmasin. Ada kendala dalam penerapan pertanggungjawaban korporasi, yang menjadi permasalahan dalam artikel ini. Data yang digunakan dalam penulisan artikel ini sebagian diperoleh dari hasil penelitian di Provinsi Sumatera Utara dan Jawa Timur. Dalam pembahasan, diuraikan ketidaklengkapan ketentuan mengenai pertanggungjawaban pidana korporasi dalam UU Tipikor yang menimbulkan kendala dalam penerapannya. Peraturan Jaksa Agung Nomor PER-028/A/JA/10/2014 tentang Pedoman Penanganan Perkara Pidana dengan Subjek Hukum Korporasi dan Peraturan Mahkamah Agung Nomor 13 Tahun 2016 tentang Tata Cara Penanganan Tindak Pidana oleh Korporasi dianggap dapat mengisi kekosongan hukum dalam menjerat korporasi sebagai subjek hukum pidana. Namun, kedudukan Peraturan Jaksa Agung dan Peraturan Mahkamah Agung tidak termasuk dalam jenis dan hierarki peraturan perundangundangan, hanya diakui keberadaannya, sehingga hanya mengikat ke dalam. Artikel ini diharapkan dapat menjadi bahan masukan dalam melakukan perubahan terhadap UU Tipikor, KUHP, dan Undang-Undang Nomor 8 Tahun 1981 tentang Hukum Acara Pidana.